Current Status of Testing and Research on Circuit Breaker Mechanical Performance and Arc Extinction. (September 2020) - Sun, Dong; Man, Xiaoping; Wang, Chuqiao; Wang, Shujie
Abstract: The performance of the circuit breaker mainly includes mechanical performance and arc extinguishing performance. This paper reviews the current status of its detection methods. Research indicates that the dynamic characteristic instrument method can meet the needs of offline detection for the detection of mechanical properties, but it cannot be implemented with electricity. The traditional method for detecting the degree of contact ablation is the electrical life method, which determines the change in the degree of contact ablation of the high-voltage reactive switching switch by the weighted calculation of the number of breaking and the breaking current. This method can only reflect the deterioration of the contact ablation degree of the high-voltage reactive switching switch, but it cannot reflect the abrupt or abnormal contact ablation degree deterioration. It is necessary to carry out research on new technology for live detection of circuit breaker performance.